Grain yield improvement in high-quality rice varieties released in southern China from 2007 to 2017 - Wang, Haixia; Xiong, Ruoyu; Zhou, Yanzhi; Tan, Xueming; Pan, Xiaohua; Zeng, Yongjun; Huang, Shan; Shang, Qingyin; Xie, Xiaobing; Zhang, Jun; Zeng, Yanhua (Frontiers in Sustainable Food Systems, 2022)
In recent years, high-quality rice varieties have been widely cultivated for food production in southern China. However, changes in the yield performance of different high-quality rice varieties are still unclear. In this study, the yield and yield components of 710 different types (hybrid or inbred rice and japonica or indica) of high-quality rice varieties were investigated in six provinces from 2007 to 2017. The results showed that, from 2007 to 2017, the grain yield and yield traits, including the number of spikelets per panicle and seed-set percentage, of high-quality indica rice varieties increased significantly, while the number of panicles decreased only in indica inbred rice. The grain yield of high-quality japonica rice also increased significantly, whereas japonica hybrid rice increased the number of spikelets per panicle and decreased the number of panicles. Compared with inbred rice, hybrid rice had a significant increase in grain yield due to a higher number of spikelets, rather than a lower number of panicles and seed-set percentage. Meanwhile, japonica rice showed higher grain yield than indica rice, which was attributed to seed-set percentage and an optimized structure between the number of panicles and the number of spikelets. In addition, the coefficient of variation of the grain yield of japonica rice decreased, whereas that of indica rice increased over time, and those of the number of panicles and seed-set percentage remained stable. Among the six provinces, Zhejiang had the highest grain yield because the number of spikelets per panicle and seed-set percentage increased over time. Our results suggested that, based on an increase in the yield potential of high-quality rice varieties over the past 11 years, future breeding of high-quality rice should be emphasized to improve the number of panicles and seed-set percentage for hybrid rice and the number of spikelets for inbred rice, especially the grain weight for indica inbred rice.